PENGARUH EDUKASI MENGGUNAKAN KARTU POHON KELUARGA (KPK) TERHADAP TINGKAT PENGETAHUAN DAN PERILAKU PENCEGAHAN DIABETES MELLITUS PADA ANGGOTA KELUARGA - Tri Yuliasih (FK IK UMY 2016, 2016)
Background: Diabetes mellitus and its complications has become a serious public health problem and an important cause of morbidity, mortality and disability worldwide. There are approximately 46% of people who suffer from undiagnosed diabetes mellitus around the world. In Indonesia, about 75% of people with diabetes do not know that he was suffering from diabetes melitus and end up not getting enough of treatment and care. Diabetes mellitus is a disease that tends to be inherited and is not a contagious disease. A history of diabetes mellitus in the family increases the risk of someone to suffer diabetes mellitus later in life compared with those without a family history of diabetes. Awareness for prevention (early detection) in the community is still lacking, thus a media such as Kartu Pohon Keluarga is expected to increase awareness of family members at risk in order to make prevention. Methods: The method used in this study was quasy experiment design with pretest and posttest control group design. Total samples of 34 people in Puskesmas Kasihan Bantul were divided into a control group and intervention group. The education given to the intervention group was twice within one month. The level of knowledge and prevention of diabetes mellitus behavior was assessed using a questionnaire which validity and reliability have been tested previously in Puskesmas Sedayu I. Results: Wilcoxon test result for the level of knowledge showed the p value (sig) p = 0.172 (> 0.05) in the control group and paired T test in intervention group showed p = 0.000 (<0.05). As for the behavior, the paired T test showed the p value (sig) p = 0.431 (> 0.05) in control group and p = 0.000 (<0.05) in intervention group. The results above indicated that there was no significant result in the control group, otherwise, the intervention group showed a significant result. Conclusion: Education using Kartu Pohon Keluarga affects the level of knowledge and prevention behaviors of diabetes in family members with significant value of 0.000 (p <0.05). Keywords : Education, Kartu Pohon Keluarga, level of knowledge, behaviour, prevention of diabetes mellitus